"Un interessante caso di spasma da torsione": sapere medico e documentario sperimentale nel Guf di Perugia (Schermi. Storie e culture del cinema e dei media in Italia, 2019)
Over the backdrop of a reflection on the almost absolute centrality of documentary practice in the complex jumble of experimental Cineguf productions between 1934 and 1943, the essay examines the only remaining neuropathological documentary produced within a Cineguf: “Un interessante caso di spasma da torsione” (1937, by Mario Bencivenga). Shot in the Santa Margherita Psychiatric Hospital in Perugia, the film documents a young girl in the grip of a series of dramatic spasms, due to a case of dystonia. This documentary is an exceptional testimony to the vitality and richness of the scientific documentary debate in the Cineguf and to the convergence of experimental and substandard film practices and scientific research. Studying it therefore reveals traces of a complex etiological debate, between neurology and psychoanalysis, where dystonia becomes the terrain for an epistemological clash that leaves traces in the film.